EFFECT OF DIGITAL MARKETING ON PURCHASING DECISIONS FOR TYPICAL BIMA FOOD PRODUCTS - SRI ERNAWATI (Program Sarjana Manajemen Universitas Internasional Batam, 2023)
Companies that can compete in a competition are companies that can apply technology in their companies. One of the factors supporting the success of companies and entrepreneurs to gain profits in a wider scope, for this reason one of the strategies that is widely used by entrepreneurs in trading is through digital marketing. This study aims to determine whether there is a significant influence of digital marketing on purchasing decisions for typical Bima food products. The research instrument used a questionnaire with a Likert scale. Data collection techniques using observation, questionnaires and literature study. Data analysis validity, reliability, simple regression test, correlation test, determination test and t test. The results of the study show that digital marketing has a significant effect on purchasing decisions for typical Bima food products